Investigating adult’s decisions to permit children access to online social networks : theory and empirical tests. - Mohamad Faizal Abdolah. (2009)
With the advent of Web 2.0, many social networking sites have emerged on the internet. Some of these sites are targeted at young children. The purpose of this study was to examine the perspectives of adults in Singapore towards the use of towards the use of online social networks by young children. A theoretical model based on Theory of Planned Behaviour (Ajzen, 1991) was developed to determine the factors that contribute towards an adult’s decision–making process in allowing young children access to online social networks. Both qualitative and quantitative research methodologies were used in this study. Findings indicate that adults perceive more danger than benefits for young children to access these sites. Also, the behavioural intention of adults to provide permission to young children to access online social networks depends primarily on their perceived role. A number of implications for site developers, parents, educators and children watch groups are drawn based on the findings.